ANALISA DESIGN UI/UX APLIKASI REKRUITMENT PADA PT. TERRA SAMUDRA JAYA SOLUSINDO - Mustika, Wida Prima; Sudrajat, Budi; Lase, Mareanus (Jurnal Manajamen Informatika Jayakarta, 2024)
The most important component in a company is Human Resources (HR) to support the execution of the company's operational functions. With quality HR and high competence, the company's goals can be realized. As an initial step to acquire the necessary human resources, it is through the organization of new employee recruitment activities. This research uses a user-oriented Design Thinking method. This method has 5 stages in the process, namely Empathize, Define, Ideate, Prototype, and Testing. After successfully completing those 5 stages, the author then conducted usability testing using the System Usability Scale (SUS) method, which resulted in an average score of 82. Based on the interpretation of the SUS score, this value falls into grade A, where the score obtained is above the general average SUS score of 68.